The effect of pace on stride characteristics and variability in sprint running - Wilson, C.; Gittoes, M.; Heywood, P. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The purpose of this study was to investigate the influence of sprint running pace on stride characteristics and their associated variability. Stride characteristics were determined for four experienced male track athletes during sprint running trials at three specified paces. The influence of pace on the stride length and frequency were investigated along with the within subject coefficient of variation for the step frequency / length ratio and the stride velocity. Stride length and stride frequency were shown to influence velocity the greatest at the slowest and fastest paces respectively. Variability of the stride frequency / length ratio was shown to increase with pace whereas the variability of the stride velocity was shown to decrease with pace. Variability within the stride characteristics suggests athletes adopt a flexible control strategy which can adapt to potential perturbations.